Evaluation of the Efficacy of Neo-endo, Hyflex Re-treatment File Systems and H-Files for Removing Gutta-Percha From Root Canal Treated Tooth by Using Stereomicroscope-An In Vitro Study - Karunakar P; Ranga Reddy M S; Karteek Basa Srinivas; Lakshmi Charan Reddy Chavva; Swetha Chigurupati; Racha Kundana; Waheed Sumaiya (Wolters Kluwer Medknow Publications, 2024)
AimTo evaluate the efficacy of Neo-endo, Hyflextm retreatment file systems, and H-files for removing gutta-percha from root canal treated tooth. Materials and MethodsThirty extracted single-rooted human teeth with a single canal were opted. The shaping of the root canals was done with pro-taper universal files and later obturated. The samples were grouped based on the file system chosen for removing the obturating material: Group I-H-files; Group II-Neo-endo retreatment files; Group III-Hyflex™ retreatment files. The quantity of remaining gutta-percha still present after the retreatment procedure was assessed under a stereomicroscope. One-way Analysis of Variance (ANOVA) was used to statistically analyze the data. ResultsHyflex™ files left less remaining filling material than with Neo-endo and H-files. ConclusionThe Hyflex™ retreatment files were most efficient in removing the gutta-percha from the root canal.